2020
DOI: 10.1038/s41467-020-17148-x
|View full text |Cite|
|
Sign up to set email alerts
|

Engineering monocyte/macrophage−specific glucocerebrosidase expression in human hematopoietic stem cells using genome editing

Abstract: Gaucher disease is a lysosomal storage disorder caused by insufficient glucocerebrosidase activity. Its hallmark manifestations are attributed to infiltration and inflammation by macrophages. Current therapies for Gaucher disease include life−long intravenous administration of recombinant glucocerebrosidase and orally-available glucosylceramide synthase inhibitors. An alternative approach is to engineer the patient's own hematopoietic system to restore glucocerebrosidase expression, thereby replacing the affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…Therapeutic transgenes involved in lysosomal storage disorders were inserted in the CCR5 gene of human HSC, under the control of exogenous ubiquitous or tissue-specific promoters. Upon transplantation, edited HSC engrafted, differentiated, and corrected the pathological phenotype in mouse models of MPS I (Gomez-Ospina et al, 2019 ) and Gaucher (Scharenberg et al, 2020 ). Although promising, the safety of this approach needs to be further validated, as CCR5 deficiency can result in increased susceptibility to West Nile (Lim et al, 2006 ; Cahill et al, 2018 ), influenza (Falcon et al, 2015 ), and Japanese encephalitis viruses (Larena et al, 2012 ).…”
Section: Safe Genomic Harborsmentioning
confidence: 99%
“…Therapeutic transgenes involved in lysosomal storage disorders were inserted in the CCR5 gene of human HSC, under the control of exogenous ubiquitous or tissue-specific promoters. Upon transplantation, edited HSC engrafted, differentiated, and corrected the pathological phenotype in mouse models of MPS I (Gomez-Ospina et al, 2019 ) and Gaucher (Scharenberg et al, 2020 ). Although promising, the safety of this approach needs to be further validated, as CCR5 deficiency can result in increased susceptibility to West Nile (Lim et al, 2006 ; Cahill et al, 2018 ), influenza (Falcon et al, 2015 ), and Japanese encephalitis viruses (Larena et al, 2012 ).…”
Section: Safe Genomic Harborsmentioning
confidence: 99%
“…We, therefore, consider this cell type to be of special relevance for clinical research, not only for its expected uptake of formulated IVT-mRNA even if not specifically targeted, 34 but also because of its considerable immune-modulatory capacity, 35,36 as well as its ability to initiate and modulate antiviral or anti-tumor T cell responses 37,38 as antigen-presenting cells, 39 and as a potential direct target in addressing macrophage-related diseases. 40 We postulated that systematic analysis of different 5 0 -end and internal nucleotide modifications of IVT-mRNA transfected in human mac- rophages reveals the pattern of cellular response, which could be harnessed to minimize or potentially abrogate the subsequent immune response (Figure 1). In a comprehensive side-by-side study, mRNA constructs with three distinct cap structures, with or without extra phosphatase treatment, were investigated in parallel with three different uridine modifications and one cytidine modification; see Figure 2 and Table S1 for details of mRNA synthesis process and chemistry, and Figure S1 for precise chemical formula of cap and nucleoside modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that CRISPR-Cas9 can successfully delete a large fragment at the β-globin locus, reactivating fetal γ-globin expression in adult erythroblasts and reversing sickle cell disease and β-thalassemia [63,64]. Similarly, knock in of the glucocerebrosidase gene within hematopoietic stem cells restores enzyme function in a Gaucher disease model [65]. CRISPR-Cas9 therapy was also useful in X-linked chronic granulomatous disease (X-CGD), in which correction of the CYBB mutations within immune cells produced functional human myeloid and lymphoid cells in a mouse model [66].…”
Section: Removal Of Cellsmentioning
confidence: 99%